PENGEMBANGAN VIDEO PEMBELAJARAN INTERAKTIF DENGAN PENDEKATAN DEMONSTRASI PADA MATA PELAJARAN PENDIDIKAN PANCASILA SD NEGERI 1 LUBUK MAKMUR - sitirahayu; Neta Dian Lestari; Sri Wahyuningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce interactive learning video products with a demonstration approach on Pancasila education subjects that meet the criteria of valid, practical, and effective. The type of research used is Research and Development development research. The researcher used the 4D development model (Define, Design, Development, Disseminate). The subjects of this study were grade III students of SD Negeri 1 Lubuk Makmur, OKI. The results of several experts stated that the product developed by the researcher was declared very valid, obtaining an average value of 91%, with this the product the researcher made was worthy of use in research, from the results of the questionnaire responses of grade III students, namely at the one-two-one stage, the small group stage, and teacher responses obtained an average score of 90% very practical. The results of the potential effect, the results of the pretest score obtained a percentage score of 63.48% with high criteria, while the results of the posttest obtained a percentage score of 89.46% very high.